Burden of Placental Malaria among Pregnant Women Who Use or Do Not Use Intermittent Preventive Treatment at Mulago Hospital, Kampala. (13th December 2016) - Odongo, Charles Okot; Odida, Michael; Wabinga, Henry; Obua, Celestino; Byamugisha, Josaphat
Abstract : Intermittent preventive treatment of malaria in pregnancy with sulphadoxine-pyrimethamine (SP-IPTp) is widely used to reduce the incidence of adverse pregnancy outcomes. As a monitor for continued effectiveness of this intervention amidst SP resistance, we aimed to assess malaria burden among pregnant women who use or do not use SP-IPTp. In a descriptive cohort study at Mulago Hospital, Kampala, 87 women who received two supervised doses of SP-IPTp were followed up until delivery. Controls were pregnant women presenting in early labour without history of SP-IPTp. Histopathological investigation for placental malaria (PM) was performed using the Bulmer classification criterion. Thirty-eight of the 87 women returned for delivery and 33 placentas were successfully collected and processed along with 33 placentas from SP nonusers. Overall, 12% (4/33) of the users had evidence of PM compared to 48% (16/33) of nonusers. Among nonusers, 17/33, 8/33, 2/33, and 6/33 had no placental infection, active infection, active-chronic infection, and past-chronic infection, respectively. Among users, respective proportions were 29/33, 2/33, 0/33, and 2/33. No difference in birth weights was apparent between the two groups, probably due to a higher proportion of infections occurring later in pregnancy. Histological evidence here suggests that SP continues to offer substantial benefit as IPTp.